Anatomy of a public-private partnership: Hold-up and regulatory commitment in Ultrafast Broadband. (August 2018) - Howell, Bronwyn; Sadowski, Bert
Abstract: In recent years, the preference for purely private funding and ownership of telecommunications networks has given way to a 'new wisdom' that some form of public funding is now likely necessary if faster and more capacious next generation access (NGA) networks are to be constructed in a timely fashion for the majority of the population. Policy-makers are charged with deciding how that public investment will take place. One approach is via Public-Private Partnerships (PPPs), where public and private actors collaborate in UFB (Ultrafast Fibre Broadband) investment, construction and operation. However, the body of analysis of PPPs in NGA networks to guide policy-makers is scant. By using the concept of regulatory commitment, the paper compares the experiences gained in a hold-up situation in PPPs in other infrastructures (e.g. roading) with the UFB context. A case study of New Zealand's Ultrafast Fibre Broadband Initiative is used to draw new insights for government purchasers and regulatory agencies. In comparing the different forms of PPPs, the paper shows that UFB PPPs reverse the typical direction of financing and ownership observed in roading PPPs. Financing and asset ownership are separated in UFB PPPs, increasing the potential for misalignment of incentives and the likelihood that the public party can use its legislative powers to alter regulatory settings after the PPP contract is signed, and thereby hold up the private party once existing network assets are sunk. Whilst the government instigating the PPP may not be inclined to act opportunistically, a successive government facing different political priorities does not face the same incentives. To the extent that the private party can anticipate this risk, it should structure the initial agreement to ensure that the public party is penalised if such an event occurs (i.e. an automatic right to favourable renegotiation or payment of compensation). Such terms will discourage opportunism, so that the project benefits from time-consistent alignment of incentives and objectives. Highlights: Ultrafast Broadband PPPs reverse hold-up risk relative to roading PPPs. Regulatory commitment provides insufficient safeguards for private party. Government-as financier has different incentives from government-as regulator. Government opportunism evidenced in NZ case study. Risk mitigated by favourable private renegotiation terms if regulations change.